2006
DOI: 10.1596/1813-9450-4054
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance And Shariah Compliance In Institutions Offering Islamic Financial Services

Abstract: Corporate Governance and Shariah Compliance in Institutions Offering Islamic Financial ServicesThe structures and processes established within an Instiution Offering Islamic financial Services (IIFS) for monitoring and evaluating Shariah compliance rely essentially on arrangements internal to the firm. By being incorporated in the institutional structure, a Shariah Supervisory Board (SSB) has the advantage of being close to the market. Competent, independent, and empowered to approve new Shariah-conforming ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
164
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(169 citation statements)
references
References 3 publications
4
164
0
1
Order By: Relevance
“…It has often been mentioned in extant literature that Shari'a scholars lack expertise in the banking sector (Farook and Farook, 2011, Karim and Archer, 2007, El Tiby, 2011, Grais and Pellegrini, 2006b, Grais and Pellegrini, 2006a, Ghoul, 2008 which makes it easy for bankers to get Shari'a certification from jurists by reengineering the complex financial products in a way that seems Shari'a compliant (El-Gamal, 2005, El-Gamal, 2006). Karim and Archer (2007) asserted that in many cases Islamic banks did not select Shari'a scholars based on their knowledge and expertise in the areas of banking and Shari'a but exclusively on their market reputation.…”
Section: Capacity Gapmentioning
confidence: 99%
“…It has often been mentioned in extant literature that Shari'a scholars lack expertise in the banking sector (Farook and Farook, 2011, Karim and Archer, 2007, El Tiby, 2011, Grais and Pellegrini, 2006b, Grais and Pellegrini, 2006a, Ghoul, 2008 which makes it easy for bankers to get Shari'a certification from jurists by reengineering the complex financial products in a way that seems Shari'a compliant (El-Gamal, 2005, El-Gamal, 2006). Karim and Archer (2007) asserted that in many cases Islamic banks did not select Shari'a scholars based on their knowledge and expertise in the areas of banking and Shari'a but exclusively on their market reputation.…”
Section: Capacity Gapmentioning
confidence: 99%
“…In this way, the so-called 'Shariah risk', i.e. the risk that a transaction judged to be Shariah compliant by the scholars of an Islamic Bank may be unlawful according to the scholars of another Islamic Bank, is prevented, despite the fact that both banks operate in the same country (Grais & Pellegrini, 2006;Casper, 2012;Ginena, 2014). As far as the two European cases are concerned, there is clearly no central authority to which to entrust this function.…”
Section: Results: a Comparative Analysis Of The Examined Casesmentioning
confidence: 99%
“…The Shariah Supervisory Board performs the following three principal functions (Grais & Pellegrini, 2006;Casper, 2012, Ginena & Hamid, 2015Mohamad, Sori & Rasid, 2017): The certification function of the SSB is considered the most relevant for the Islamic Bank, as it is necessary to prove the bank's religious integrity and for it to have a good reputation. The certification takes place through the discussion and issuance of opinions on the effective compatibility of the implemented transactions and of the various Islamic financial products that are offered with the Shariah's approval.…”
Section: Results: a Comparative Analysis Of The Examined Casesmentioning
confidence: 99%
“…In addition, it defeats the purpose of maq a Á sid al-Sharīʿah (objectives of Islamic law), namely, the preservation of public interest (Hassan and Mahlknecht, 2011;Zuhaili, 2013). Moreover, the General Council for Islamic Banks and Financial Institutions (CIBAFI) has also reported that out of a set of 6,000 fatwas issued by IFIs worldwide, inconsistent fatwas across the globe only accounted for 10 per cent or approximately 600 fatwas (Grais and Pellegrini, 2006;Devi, 2008). In other words, strong evidence exists to indicate the existence of a near consensus among Sharīʿah scholars on a majority of Sharīʿah issues in Islamic banking.…”
Section: Diversity Of Sharīʿah Opinions In Islamic Bankingmentioning
confidence: 99%